2018
DOI: 10.3390/molecules23112807
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Osteoarthritis-Related Molecules by Isomucronulatol 7-O-β-d-glucoside and Ecliptasaponin A in IL-1β-Stimulated Chondrosarcoma Cell Model

Abstract: Osteoarthritis (OA) is the common form of arthritis and is characterized by disability and cartilage degradation. Although natural product extracts have been reported to have anti-osteoarthritic effects, the potential bioactivity of Ryupunghwan (RPH), a traditional Korean medicinal botanical formula that contains Astragalus membranaceus, Turnera diffusa, Achyranthes bidentata, Angelica gigas, Eclipta prostrata, Eucommia ulmoides, and Ilex paraguariensis, is not known well. Therefore, the inhibitory effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…Thus, we hypothesized that TLR4/Akt/FoxO1 axis exists in OA and resveratrol may exert anti-osteoarthritic effect, at least in part by enhancing TLR4/Akt/FoxO1 axis, thereby decreasing TLR4 expression and subsequent TLR4/NF-κB signaling pathway suppression. To address this, in the present study, we mimic OA state by stimulating SW1353 cells with IL-1β 29 to verify our hypothesis "in vitro".…”
Section: Introductionmentioning
confidence: 96%
“…Thus, we hypothesized that TLR4/Akt/FoxO1 axis exists in OA and resveratrol may exert anti-osteoarthritic effect, at least in part by enhancing TLR4/Akt/FoxO1 axis, thereby decreasing TLR4 expression and subsequent TLR4/NF-κB signaling pathway suppression. To address this, in the present study, we mimic OA state by stimulating SW1353 cells with IL-1β 29 to verify our hypothesis "in vitro".…”
Section: Introductionmentioning
confidence: 96%
“…However, despite these various biological activities, prenylated xanthones have not been studied for OA. Previous studies have shown that hypoxia or inflammatory induction of SW1353 chondrocytes stimulated by IL-1β, monosodium iodoacetate (MIA), and H 2 O 2 is known as a representative in vitro model for OA studies [ 20 , 21 , 22 , 23 ]. In this study, we investigated the role of prenylated xanthones, cudratricusxanthone O (CTO), isolated from M. tricuspidata , on the suppression of H 2 O 2 -induced cell damage by promoting the Nrf2/HO-1 pathway in SW1353 cells.…”
Section: Introductionmentioning
confidence: 99%
“…The formula contains a number of natural products, such as Astragalus membranaceus, Turnera diffusa, Achyranthes bidentata, Angelica gigas, Eclipta prostrata, Eucommia ulmoides, and Ilex paraguariensis, most of which are traditionally used in folk medicine. The formula was tested in the context of positive properties against OA, via in vitro experiments on cellular IL-1β-stimulated chondrosarcoma, SW1353 cell model [82]. As reported in this recent work, the pre-treatment with RPH had a suppressive effect on the mediators that contributed to the progression of osteoarthritis by inhibiting collagen 2, COX-1-2, MMP-13, TNF-α, and IL-13 expression [82].…”
Section: Ryupunghwanmentioning
confidence: 94%
“…In a recent study, Hong G.U. et al presented the OA modulating potential of a botanical formula, which is particularly common in Korea, mostly well known as Ryupunghwan (RPH) [82]. The formula contains a number of natural products, such as Astragalus membranaceus, Turnera diffusa, Achyranthes bidentata, Angelica gigas, Eclipta prostrata, Eucommia ulmoides, and Ilex paraguariensis, most of which are traditionally used in folk medicine.…”
Section: Ryupunghwanmentioning
confidence: 99%
See 1 more Smart Citation